HUBUNGAN PELAKSANAAN KELAS IBU HAMIL DENGAN PEMANFAATAN BUKU KIA DI WILAYAH PUSKESMAS 1 SOKARAJA KABUPATEN BANYUMAS - Khamidah Achyar (Viva Medika, 2020)
The implementation of pregnant mothers class program activities based on the results of research around 35% -100%, these activities in various regions in Indonesia have not been evenly distributed, as well as the use of the MCH handbook. Based on national health survey data (Sirkesnas 2016) that pregnant women who have MCH books are 81.5% but only 60.5% of them can show MCH handbook. The purpose of this study is to determine the relationship between the implementation of classes of pregnant women with the use of the MCH handbook in the working area of ​​the Puskesmas 1 Sokaraja. The sample in this study were pregnant women who took the class of pregnant women totaling 40 respondents. Research design using Crossectional. The results of this study are respondents who attend the class of pregnant women and use the MCH book as much as 80% and who often attend the class of pregnant women using the MCH book as much as 50%. The results of the analysis there is no relationship between the implementation of classes of pregnant women with the use of the MCH book (ρ = 0.057) Conclusion: There is no relationship between the implementation of the class of pregnant women with the use of the MCH handbook